2021
DOI: 10.21474/ijar01/13873
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Use of Icts in Accessing E-Extensionservices Among Smallholder Farmers in Nakuru County, Kenya

Abstract: Smallholder farmers in Kenya are faced with low agricultural productivity which has been attributed toa number of factors among them being lack of access to agricultural information. This has been further exacerbated by shrinking number of public extension staff and underfunding of the extension system in the country. ICTs can play a crucial role in bridging this gap. This study determined ICTs accessed, and the extent of use of the ICTs to access e-Extension services among smallholder farmers in Nakuru county… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This indicates that older farmers are less likely to access CIS, which is a crucial element tied to agricultural experience (Muema et al, 2018). This result agrees with the findings of Yong (2014), Kirui et al (2014), Onyeneke et al (2023), and Muema et al (2018), proving that older farmers have improved their climate observation and risk dissemination skills Indigenously, resulting in a lower demand for CIS. Although older household heads manage several adaptation strategies in the active workforce, young household heads apply various climate adaptation techniques more frequently than older household heads (Megabia et al, 2022).…”
Section: Resultssupporting
confidence: 91%
“…This indicates that older farmers are less likely to access CIS, which is a crucial element tied to agricultural experience (Muema et al, 2018). This result agrees with the findings of Yong (2014), Kirui et al (2014), Onyeneke et al (2023), and Muema et al (2018), proving that older farmers have improved their climate observation and risk dissemination skills Indigenously, resulting in a lower demand for CIS. Although older household heads manage several adaptation strategies in the active workforce, young household heads apply various climate adaptation techniques more frequently than older household heads (Megabia et al, 2022).…”
Section: Resultssupporting
confidence: 91%
“…This suggests that a large majority of the respondents were smallholders. Group membership as depicted by the results indicated that 63 percent of respondents were members of a farmer group organization while 37 percent were not affiliated to any farmer group organization" [8].…”
Section: Resultsmentioning
confidence: 98%
“…The distribution of respondents by education level indicates that 66 percent had attained primary level of education, 45 percent having attained secondary level and only 9 percent reaching the tertiary and university level". [8] "However, 5 percent of the respondents had no education at all. The overall findings therefore, shows that majority of the respondents had attained primary level of education and are able to read and write which could influence their ability to use ICT tools to access agricultural information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation